The Oxford handbook of management ideas - Sturdy, Andrew; Heusinkveld, Stefan; Reay, Trish; Strang, David (Oxford : Oxford University Press, 2019)
Management ideas, and their associated applications, have become a prevalent feature of our working lives. While their focus is familiar, such as efficiency, motivation, and improvement, they range from specific notions such as activity-based costing, to broad movements like corporate social responsibility. Providing an up to date, enduring, and authoritative account of the field of research on management ideas, this work addresses questions of where management ideas come from, how they are produced, promoted and used, and their effect on business and working practices.
Evolving management ideas / Hannele Seeck, Juha-antti Lamberg -- Management's gurus / David Collins -- Business media: From Gatekeeping to Transmediality / Marco Barros, Charles-Clemens Rüling -- Thought leaders and followers: the impact of consultants and advisers on management ideas / Christopher Wright -- Business studies and management ideas / Lars Engwall, Linda Wedlin -- Multinational and Transnational Organizations: The Role of Globalizing Actors / Philipp Kern, Phil Almond, Tony Edwards, Olga Tregaskis -- The Consumers and Co-Producers of Management Ideas / Suleika Bort, Alfred Kieser -- The Re-adoption of Management Ideas: How They Come, How They Go, and Why Some Come Back / Patrick Reinmoeller, Shahzad Ansari, Mohit Mehta -- Management Ideas as Standards / Andreas Rasche, David Seidl -- Understanding and Analysing Resistance to Management Ideas / Darren McCabe, Sylwia Ciuk, Stephanie Russell -- Popular management ideas / Helene Giroux -- The performance implications of management ideas / Christopher Wickert, Jost Sieweke, Riku Ruotsalainen -- The (Geo)-Politics of Management Ideas - Three Moments in the Trajectory of an Instrument of Power / Marie-Laure Salles-Djelic -- The Role of Family Firms in Corporate Sustainability / Pramodita Sharma, Sanjay Sharma -- Managing Public Service Professionals under New Public Management / Michael Reed -- Instrumental understanding of management ideas / Kjell-Arne Røvik -- Management ideas in everyday life / Philip Hancock, Melissa Tyler -- Changing the critique: From Critical Management Studies to Activist Scholarship / Craig Prichard, Ozan Alakavuklar -- Alternatives to management ideas / Martin Parker -- Management Ideas and the Social Construction of Organizations / Shawn Pope, Patricia Bromley -- The system of management ideas: Origins, Microfoundations, and Dynamics / Michael Mol, Julian Birkinshaw, Nicolai J. Foss -- New Direc
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 2, 2019).
Keywords: Management -- Philosophy